A comparison of the performances of polypropylene and rubber fibers in completely decomposed granite. Issue 1 (February 2018) - Fu, R.; Baudet, Béatrice A.; Madhusudhan, B.N.; Coop, M.R.
Abstract: This fundamental study investigates how two very different types of fibers, very elongated polypropylene fibers with high tensile resistance, and larger rubber fibers with a smaller aspect ratio and low shear and Young's moduli affect the compression and shearing of a soil. The same host soil was used for both types of fibers, a well-graded decomposed granite. As well as providing a realistic base for the study with its well graded nature, the decomposed granite's tendency to contract upon shearing is used to highlight the underlying mechanisms causing any difference in behavior. The soil mixtures were prepared at an optimal fiber content for each kind. The general patterns of behavior of the reinforced soils, such as the stress-dilatancy behavior, and the normal compression and critical state lines, are compared. It is found that the specimens with rubber fibers are initially much less stiff than those with polypropylene fibers, so that they require larger deformations to reach failure. At failure, they can provide as much extra strength as polypropylene fibers if the rubber fiber-soil mixture has been consolidated to a low confining stress, although very much larger quantities are needed, even to the point of being unrealistic for engineering applications. At high confining pressures, the rubber fibers, which have become slack during compression, tend to lose in efficiency. The soil reinforced with polypropylene fibers develops consistently higher strength, but the compressive nature of the base soil has the effect of hindering their full mobilization as would be seen in a dilative soil.